Optimalisasi Pendayagunaan Dana ZIS (Zakat, Infaq, Sedekah) Melalui Program Rumah Singgah Pasien di LAZNAS IZI Jawa Timur - Fatchiatul Ma’rifah; Ahmad Ajib Ridlwan (Inspirasi Nusantara, 2022)
Indonesia experiences various problems from various aspects of life, including one in the health sector. The purpose of this study is to optimize the management of ZIS funds so that they can be efficient and able to contribute to the reduction of existing health and poverty problems. The research method used is descriptive qualitative method. The data collection techniques used in the study were interviews and documentation. The unit of research analysis was LAZNAS IZI Jatim as the provider of the Patient Shelter Program. Based on the results and discussions that have been found by researchers, researchers can conclude that RSP IZI Jatim has utilized ZIS funds in the Patient Shelter House program by providing assistance in the form of housing, consumption, patient transportation accommodation in the form of ambulans, and various positive activities for patient. RSP IZI Jatim also carried out various strategies to optimize the utilization of ZIS funds for the RSP IZI Jatim. In addition, the supporting and inhibiting factors also help RSP IZI Jatim in understanding how to optimize what needs to be done